Development of oil cells and ducts in ginger (Zingiber officinale Rose.) - RAVINDRAN, A B REMASHREE, K UNNIKRISHNAN, P N (Journal of Spices and Aromatic Crops, 1999)
The development, distribution and structure of oil cells, development of secretory ducts and diffusion of oil in ginger rhizomes (Zingiber officinale) were studied. Oil cell differentiation initiate from a group of meristematic cells before the development of primary vascular tissue. Oil cells are present in leaf, shoot apex, root apex and are more or less spherical and contain stored volatile oil. The number of oil cells is higher in the apical and nodal regions than in the internodal region and the size of oil cells is dependent on their number. Secretory ducts develops schizogenously and lysigenously. The former type is present in the primary tissues while the latter type is found throughout the developmental stages.